A review of natural products as a source of next-generation drugs against apicomplexan parasites - Emma Y. Mao; Stephen W. Page; Brad E. Sleebs; Maria R. Gancheva; Danny W. Wilson (npj Antimicrobials and Resistance)
Abstract Despite the substantial global health and economic burden of apicomplexan parasites in humans and livestock, treatment options remain limited. Natural products have long played an important role in combating these diseases, offering diverse chemical structures and bioactive compounds. This review summarises past and present natural-product-based therapies for six economically significant apicomplexans and explores the potential of revisiting natural products as a source of next-generation treatments.